A Haloalkane Dehalogenase from a Marine Microbial Consortium Possessing Exceptionally Broad Substrate Specificity - Buryska, Tomas; Babkova, Petra; Vavra, Ondrej; Damborsky, Jiri; Prokop, Zbynek (Applied and environmental microbiology, 2018)
The haloalkane dehalogenase enzyme DmmA was identified by marine metagenomic screening. Determination of its crystal structure revealed an unusually large active site compared to those of previously characterized haloalkane dehalogenases. Here we present a biochemical characterization of this interesting enzyme with emphasis on its structure-function relationships. DmmA exhibited an exceptionally broad substrate specificity and degraded several halogenated environmental pollutants that are resistant to other members of this enzyme family. In addition to having this unique substrate specificity, the enzyme was highly tolerant to organic cosolvents such as dimethyl sulfoxide, methanol, and acetone. Its broad substrate specificity, high overexpression yield (200 mg of protein per liter of cultivation medium; 50% of total protein), good tolerance to organic cosolvents, and a broad pH range make DmmA an attractive biocatalyst for various biotechnological applications.IMPORTANCE We present a thorough biochemical characterization of the haloalkane dehalogenase DmmA from a marine metagenome. This enzyme with an unusually large active site shows remarkably broad substrate specificity, high overexpression, significant tolerance to organic cosolvents, and activity under a broad range of pH conditions. DmmA is an attractive catalyst for sustainable biotechnology applications, e.g., biocatalysis, biosensing, and biodegradation of halogenated pollutants. We also report its ability to convert multiple halogenated compounds to corresponding polyalcohols.
Keywords: Substrate Specificity; metagenom; haloalkane dehalogenase; hydrolasy; Hydrogen-Ion Concentration; Bacteria; biokatalýza; cosolvents; marine; Biocatalysis; Kinetics; biotechnologie; substrate specificity; Hydrolases; Biotechnology; kinetika; Microbial Consortia; microbial; Metagenome; Catalysis; katalýza; substrátová specifita; Catalytic Domain; biotechnology; krystalizace; katalytická doména; stability; Crystallization; mikrobiální společenstva; koncentrace vodíkových iontů; enzyme